Makna Warna Merah dan Putih dalam Video Klip Hingga Tua Bersama Rizky Febian - Fanthony Everell; Delliana, Santi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Color is a very sensitive thing that plays an important role for someone who sees it and has various meanings in it. Including the red and white colors in the video clip "Hingga Tua Bersama". This study aims to determine the meaning of the red and white colors in Rizky Febian's video clip "Hingga Tua Bersama". In this research, the researcher used the social reality construction theory of mass media with a descriptive qualitative approach using Charles Sanders Peirce's semiotic method which has Sign, Object and Interpretant to interpret the red and white colors in the video clip. The results of this study found that the red and white colors in the video clip "Until Old Together" can be interpreted as purity, sincerity, struggle, emotion, love and innocence.